Persulfate promoted flow electrochemistry: Direct conversion of cyclohexane into adipic acid. (10th September 2022) - Tian, Hao; Zhang, Yujun; Yu, Di; Yang, Xue; Wang, Hong; Matindi, Christine; Yin, Zhen; Hui, Hongseng; Mamba, Bhekie B.; Li, Jianxin
Highlights: An ECMR with V2 O5 /Ti electrode was used to activate Na2 S2 O8 to produce AA from CYH. Na2 S2 O8 as electrolyte promoted ECMR to produce SO4 ·−, HO· and non-radicals. 68.5% CYH conversion and the selectivity to AA (53.2%) and KA oil (39.5%) achieved. The CYH oxidation is ascribed to HO· (30.7%), SO4 ·− (18.1%) and non-radicals (51.1%). High performance is due to the synergistic effect of electrolysis and PS oxidation. Abstract: A flow flow-through electrocatalytic membrane reactor (ECMR) with a nano-V2 O5 loaded porous Ti membrane (V2 O5 /Ti) as an anode and persulfate (PS) (Na2 S2 O8 ) as co-oxidants was developed for one-step production of adipic acid (AA) from cyclohexane (CYH). Electron paramagnetic resonance (EPR) spectroscopy, in-situ Raman spectroscopy as well as the corresponding electrochemical analyses were employed to investigate the production of active species and reaction mechanism. Results showed that the addition of PS significantly increased the conversion of CYH and achieved one-step oxidation of CYH (conversion:68.5%) to produce AA (selectivity: 53.2%) and KA oil (selectivity: 39.5%). The ECMR can efficiently activate PS to SO4 ·−, HO· and non-radicals (V2 O5 -PS). Besides, the direct conversion from CYH to AA was attributed to the composite electrode formed by PS and V2 O5, which can increase the open circuit potential of the working electrode. Lastly, a mechanistic pathway for the oxidation of CYH to AA was proposed. Graphical abstract: Image, graphical abstract